The Course and Anatomical Characteristics of Sciatic and Femoral Nerves in Unilateral Crowe Type-IV Hip Dysplasia - Song P; Kong X; Yang M; Ma M; Chai W (Dove Medical Press, 2022)
Ping Song,1- 3,* Xiangpeng Kong,2,3,* Minzhi Yang,2,3 Mingyang Ma,1- 3 Wei Chai2,3 1Graduate School, Chinese PLA Medical School, Beijing, People's Republic of China; 2Senior Department of Orthopedics, the Fourth Medical Center of PLA General Hospital, Beijing, People's Republic of China; 3National Clinical Research Center for Orthopedics, Sports Medical and Rehabilitation, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Wei Chai, Tel +8610-66938304, Email chaiweiguanjie@sina.comBackground: This study aims to investigate the course and anatomical characteristics of sciatic and femoral nerves in unilateral Crowe type-IV developmental dysplasia of the hip (DDH) patients.Methods: We conducted a retrospective own-control study of patients with unilateral Crowe type-IV DDH. Bilateral hip computed tomography (CT) of 21 female patients was reviewed in our institute from February 2018 to February 2020. The distances between nerves and bony landmarks were measured in different CT sections (anterior superior iliac spine, acetabular inner wall, teardrop, and ischial tuberosity) to analyze the anatomical position and course of sciatic and femoral nerves between bilateral hips.Results: In the section of the acetabular inner wall, the distance between the femoral nerve and the acetabular anterior wall in affected hip (13.20 ± 3.59 mm) was significantly smaller than that in the healthy hip (16.58 ± 5.12mm) (p < 0.001). In other sections, the distances between nerves and bony landmarks in affected hips were significantly larger than or equal to those in the healthy hips.Conclusion: In female patients with unilateral Crowe type-IV DDH, the femoral nerve in the affected hip runs closer to the anterior acetabular wall than that in the healthy hip.Keywords: developmental dysplasia of the hip, total hip arthroplasty, nerve injury, nerve course, sciatic nerve, femoral nerve